Bioresorbable Scaffolds: Contemporary Status and Future Directions - Peng, Xiang; Qu, Wenbo; Jia, Ying; Wang, Yani; Yu, Bo; Tian, Jinwei (Frontiers in Cardiovascular Medicine, 2020)
Percutaneous coronary intervention, which is safe, effective, and timely, has become an important treatment for coronary artery diseases and has been widely used in clinical practice. However, there are still some problems that urgently need to be solved. Permanent vessel caging through metallic implants not only prevents the process of positive vessel remodeling and the restoration of vascular physiology but also makes the future revascularization of target vessels more difficult. Bioresorbable scaffolds (BRSs) have been developed as a potential solution to avoid the above adverse reactions caused by permanent metallic devices. BRSs provide temporary support to the vessel wall in the short term and then gradually degrade over time to restore the natural state of coronary arteries. Nonetheless, long-term follow-up of large-scale trials has drawn considerable attention to the safety of BRSs, and the significantly increased risk of late scaffold thrombosis (ScT) limits its clinical application. In this review, we summarize the current status and clinical experiences of BRSs to understand the application prospects and limitations of these devices. In addition, we focus on ScT after implantation, as it is currently the primary drawback of BRS. We also analyze the causes of ScT and discuss improvements required to overcome this serious drawback and to move the field forward.